Do we need to vaccinate every child against COVID-19: What evidence suggests—A systematic review of opinions - Paul, Sourabh; Mishra, Chandra Mauli (Frontiers in Public Health, 2022)
It is still debatable whether all children should receive the COVID-19 vaccine. The comparatively mild cases and low risk of COVID-19 in children compared to adults, as well as the lack of clarity on the relative effects of the disease and vaccine, indicate that the risk-benefit ratio of vaccination in children is more nuanced. To consider and highlight the complexity of policy decisions regarding COVID-19 vaccination in children, we outlined the points regarding for and against vaccination of children against COVID-19 in this systemic review. Using Medical Search Headings (MeSH) terms and keywords, we searched PubMed, PubMed Central, Scopus, and Google Scholar. The primary search term was COVID-19 vaccination (all synonyms), factors (all synonyms), and among children (all synonyms). A total of 367 articles were searched. Finally, 64 articles met the inclusion criteria and were included in the review. The major theme/tone of 28 (43.75%) articles was in favor of children's COVID vaccination, and they were highlighting the positive factors, whereas the major theme/tone of 20 (31.25%) articles was against it. Approximately 16 (25.0%) articles were in a neutral position. Major factors highlighted by articles in favor of childhood COVID vaccination were as follows: the increasing rate of disease burden (29 articles), prevention of interruption of academic activities of children or school reopening (24 articles), and a role in defense against COVID infection (21 articles). Major factors against childhood vaccination were as follows: mild infection among children (27 articles), ethical concerns and legal problems regarding the consent of minors (17 articles), and vaccine hesitancy among parents for childhood vaccination (11 articles). Whereas, factors of uncertainty were the role in the reduction of community transmission (19 articles), protection against MIS-C (10 articles), and defense against long COVID (7 articles). Considering all the factors of COVID-19 disease progression among children, a cautious approach will be essential before proceeding with COVID-19 vaccination in children.